2015
DOI: 10.1371/journal.pone.0115530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Several Mutations in ATP2C1 in Lebanese Families: Insight into the Pathogenesis of Hailey-Hailey Disease

Abstract: BackgroundHailey-Hailey disease (HHD) is an inherited blistering dermatosis characterized by recurrent erosions and erythematous plaques that generally manifest in intertriginous areas. Genetically, HHD is an autosomal dominant disease, resulting from heterozygous mutations in ATP2C1, which encodes a Ca2+/Mn2+ATPase. In this study, we aimed at identifying and analyzing mutations in five patients from unrelated families diagnosed with HHD and study the underlying molecular pathogenesis.ObjectivesTo genetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Few nonsense mutations were frequently reported in different families worldwide (reports with at least three cases): 115 C > T causing R39X; 6, 18, 19 457 C > T causing R153X; 7, 20, 21, 22, 23, 24, 25 1402 C > T causing R468X; 7, 26, 27, 28 1516 C > T causing Q506X; 29, 30 and 2395 C > T causing R799X. 18, 25, 31, 32, 33, 34 The above single residues represent ‘hotspots' for mutations, and notably, they all occur at CpG sites where the possibility of mutations is higher.…”
Section: Mutations On the Human Atp2c1 Genementioning
confidence: 99%
“…Few nonsense mutations were frequently reported in different families worldwide (reports with at least three cases): 115 C > T causing R39X; 6, 18, 19 457 C > T causing R153X; 7, 20, 21, 22, 23, 24, 25 1402 C > T causing R468X; 7, 26, 27, 28 1516 C > T causing Q506X; 29, 30 and 2395 C > T causing R799X. 18, 25, 31, 32, 33, 34 The above single residues represent ‘hotspots' for mutations, and notably, they all occur at CpG sites where the possibility of mutations is higher.…”
Section: Mutations On the Human Atp2c1 Genementioning
confidence: 99%
“…In conclusion, HHD is a hereditary blistering skin disease characterized by episodic maceration and erosions mainly in intertriginous areas. Because the ATP2C1 gene was identified as the pathogenic gene of HHD, more than 150 mutations in the ATP2C1 gene have been reported, including nonsense, missense, frame‐shift and splice‐site mutations …”
Section: Discussionmentioning
confidence: 99%
“…Because the ATP2C1 gene was identified as the pathogenic gene of HHD, more than 150 mutations in the ATP2C1 gene have been reported, including nonsense, missense, frame-shift and splice-site mutations. [1][2][3][4][5][6][7][8][9][10][11][12][13] Generally, direct mutation analysis is the most powerful and conclusive means of molecular diagnosis. In our study, five different heterozygous mutations of ATP2C1 were identified in HHD patients in the four pedigrees and two sporadic cases.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the severe phenotype of a case with a PT-causing mutation is possibly caused by nonsense-mediated mRNA decay 3 . To confirm this possibility in the present case, ATP2C1 mRNA expression was examined with reverse transcription-polymerase chain reaction (RT-PCR) using mRNA extracted from the biopsy specimen and ATP2C1 -specific primer pairs which amplify an upstream portion of the mutation described elsewhere 4 . Biopsy specimen of the lesional skin from a patient with urticarial rash was simultaneously examined for the control.…”
mentioning
confidence: 92%